Estudo da estabilidade oxidativa do biodiesel de soja sob condições de armazenamento - Vale, Maria Aparecida Serejo (2011)
A relevant aspect which affects the biodiesel quality deals with it s susceptibility to oxidation. This distinctive feature is due to the presence of carbon chains like those ones of esters of unsaturated fatty acids which composes biodiesel. As it is formed the composite of degradation diminishes the oxidative stability of esters. This control reveals needs in order it can evaluated the storage conditions and avoid undesirable processes of degradations. Therefore the present paper tried to evaluate the oxidative stability of soy biodiesel, obtained through methyl and ethyl routes via basic catalysis during a period of 12 months of storage under 43ºC. The monitoring of the oxidative process occurred through not accelerated (acidity index, kinematic viscosity and relative density) and accelerated (Rancimat, PDSC and PetroOxy). The physicochemical characterization pointed that analysed parameters were found within the established limits by ANP technical regulation, except oxidative stability indexes whose values were 3,58h and 3,88h to BMS and BEE, in this succession. Chemical composition analisysis related predominance of linoleic ester in both samples (43,8 % to BMS and 45,7 to the BES) and confirmed the transformation of fatty acids in esters. The acid indexes, in both samples, presented themselves within the maximal limit demanded by the in effects resolution, increasing considerably following months. Both viscosity and density aumented in a time function, however they did not exceed the established limit by ANP. Showed to be excellent direct correlation between the acid number, viscosity and density, and these with Rancimat. In the evaluation of oxidative process, using accelerated methods, BES presented more stable to oxidation than BMS. Presenting, at the end of storage, 0.83 h by Rancimat method, 18.7 and 17.6 min for PDSC end PetroOXY, respectively.